Emotions and physical health in the second half of life: interindividual differences in age-related trajectories and dynamic associations according to socioeconomic status - Schöllgen, Ina; Huxhold, Oliver; Schmiedek, Florian (Psychology and aging, 2012)
The importance of socioeconomic status (SES) for psychological functioning over the life span is increasingly acknowledged in psychological research. The Reserve Capacity Model by Gallo and Matthews (2003) suggests that SES is not only linked to physical health but also to the experience of positive and negative emotions. Moreover, due to differential amounts of psychosocial resources, cross-domain associations between emotions and health might differ according to SES. The present study examined age-related developments in positive affect (PA), negative affect (NA), and physical health, as well as dynamic associations between health and emotions in the second half of life. We looked at differences in these trajectories and their interrelationships according to education as one aspect of SES. We used data of up to three waves spanning 12 years from the nationally representative German Ageing Survey (N = 3,847, AgeT1 = 40-85 years). Applying multiple-group dual change score models, we found differential age-related change in PA and physical health, but not in NA, in two groups differing in level of education. NA did only predict change in physical health in low-educated individuals, whereas physical health was equally strongly related to change in PA in both education groups. These results indicate that SES not only affects changes in physical health and emotional functioning but also their interrelationships.